A Life Trapped in Quotation. On Oleg Bogaev’s Comedy “How I Ate My Husband” - Graf, Alexander (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2013)
Citationality and intertextual combining of the new ‘New Drama’ form a central device of contemporary dramatic arts. In his comedy How I Ate My Husband (2009) Bogaev takes citationality to extremes and lucidly demonstrates that not only the dramatis personae but also the playwright himself, the director, and the audience are subjected to the torrent of models and pretexts largely determining the action. The whole life has frozen as if it was one big quotation running through the canvas of the dramatic text on all levels and linking the fictional life within the play to real life, combining traditional concepts of theatre with the ideas of new drama. There is no place for coincidence, it turns out that all is one persistent recurrence.